Application of Elements of Criminal Acts of Plantation Land Clearing in National Park Areas by Investigators of the South Coast Police Crime Squad - Ryki Yovrizal; Susi Delmiati (Ekasakti Journal of Law and Justice, 2023)
The South Coast Police Crime Squad conducted an investigation into the crime of carrying out plantation activities without ministerial permission in forest areas. The difficulty of the South Coast Police Detective Investigator is to implement 'Elements in forest areas'. This happened because of the unclear boundaries of the National Park forest area. In the investigation process, the Investigator applied the provisions of Article 17 paragraph (2) letter b Juncto Article 92 paragraph (1) letter a of Law Number 18 of 2013 concerning the Prevention and Eradication of Forest Destruction as Police Report Number:  LP/25/A/II/2019/ Res-Pessel dated February 12, 2019. The application of the elements of the criminal act of clearing plantation land in the National Park area consists of subjective elements and objective elements. The subjective element is a person, then what is meant by everyone in this article is the perpetrator as a person who can account  for his actions and the objective element is that his actions are unlawful, namely: "Elements intentionally, elements carrying out plantation activities,  elements without the permission of the Minister and elements dnature forest area". According to investigators, the suspect's actions have fulfilled the formulation and elements of Article 17 paragraph (2) letter b Juncto Article 92 paragraph (1) letter a of Law Number 18 of 2013.